Proses Kedewasaan Rohani Orang Kristen berdasarkan Kolose 2:6-10 - Nakmofa, Sutidjo Justus Jerzak; Mangoli, Yefta Yan (KARDIA: Jurnal Teologi dan Pendidikan Kristiani, 2023)
Abstract: This research aims to find out about the exegetical review of the process of Christian spiritual maturity based on Colossians 2:6-10, and what are the inhibiting factors for Christian spiritual growth towards spiritual maturity. The research methodology used in this research is a qualitative literature research methodology with a biblical theological research approach, through an exegetical strategy of text criticism, because the goal to be achieved is related to an exegetical review of the process of Christian spiritual maturity. The results of the discussion based on the letter Colossians 2:6-10 to the Colossians and Christians today are experiencing spiritual growth to the stage of spiritual maturity. Therefore, Christians must experience a process of spiritual maturity which includes accepting Christ, living in God, rooted in God, built up in God, growing firm in faith, hearts overflowing with thanksgiving, and experiencing the fullness of Christ (Pleroma). In undergoing the process of maturity there are obstacles that make Christians spiritually immature, including environmental influences and heretical teachings that are inconsistent with Christ's which become a snare for Christians so they do not grow towards spiritual maturity. To overcome these obstacles, Christians must build an intimate personal relationship with God through prayer, quiet time, contemplation of God's word, and spiritual discipline. Thus Christians experience Christ in his life, where Christ dwells in full control of his life as expressed by the Apostle Paul in terms of you having been filled with Christ. Abstrak: Penelitian ini, bertujuan untuk mengetahui tentang tinjuan eksegetis Proses kedewasaan rohani orang Kristen berdasarkan surat Kolose 2:6-10, dan apa saja Faktor penghambat pertumbuhan rohani orang Kristen ke arah kedewasaan rohani. Metodologi penelitian yang digunakan dalam penelitian ini adalah ialah metodologi penelitian kualitatif pustaka dengan pendekatan penelitian riset teologia biblika, melalui strategi eksegetis kritik teks, karena tujuan yang ingin dicapai sehubungan dengan tinjauan eksegetis tentang proses kedewasaan rohani orang Kristen. Adapun hasil pembahasan berdasarkan surat Kolose 2:6-10 kepada jemaat Kolose dan orang Kristen masa kini adalah mengalami pertumbuhan rohani sampai kepada tahap dewasa rohani. Oleh karena itu, orang Kristen harus mengalami proses kedewasaan rohani meliputi menerima Kristus, hidup di dalam Tuhan, berakar di dalam Tuhan, dibangun di dalam Tuhan, bertambah teguh dalam iman, hati yang melimpah dengan ucapan syukur, dan mengalami kepenuhan Kristus (Pleroma). Dalam menjalani proses kedewasaan ada hambatan yang membuat orang Kristen tidak dewasa rohani antara lain pengaruh lingkungan dan pengajaran sesat yang tidak sesuai dengan Kristus menjadi jerat bagi orang Kristen sehingga tidak bertumbuh ke arah kedewasaan rohani. Untuk mengatasi hambatan tersebut, orang Kristen harus membangun hubungan pribadi yang intim dengan Tuhan melalui doa, saat teduh, perenungan firman Tuhan, dan disiplin rohani. Dengan demikian orang Kristen mengalami Kristus dalam hidupnya, dimana Kristus berdiam secara penuh menguasai kehidupannya seperti yang diungkapkan oleh Rasul Paulus dalam hal kamu telah dipenuhi Kristus.